Juror decision-making regarding a defendant diagnosed with borderline personality disorder. Issue 4 (4th July 2022) - Baker, James; Edwards, Ian; Beazley, Peter
Abstract : Stigma is an established consequence of the Borderline Personality Disorder (BPD) diagnosis. This diagnosis is subject to revision in the International Classification of Diseases–11th Revision (ICD–11). Using the legal issue of diminished responsibility, this study applied an experimental mock-jury methodology to explore the impact of diagnostic stigma of BPD on jury decision-making. Participants were allocated to one of two versions of a simplified fictitious homicide trial. The group whose defendant was described as having a 'severe personality disorder, borderline pattern' rated the defendant as more dangerous, and more in need of segregation and coercive treatment, than controls where the defendant was described as having a 'complex mental health problem'. Between-group differences in other measures, including the decision to agree a verdict of diminished responsibility, were not found. The ICD-11 'severe personality disorder, borderline pattern' diagnosis may adversely impact the attitudes of jurors considering the question of diminished responsibility.